Ants’ Collective Intelligence: What Could We Learn? - Taw, Rodney (Science Insights, 2025)
Ants, albeit appearing diminutive and trivial within the broader context of nature, demonstrate an extraordinary capacity for collective problem-solving and exhibit intellect that beyond expectations for individual members of their species. This phenomenon, termed ants’ collective intelligence, has elicited attention and appreciation from both experts and enthusiasts. This article examines the complex mechanisms of ants’ collective intelligence, highlighting its essential features, ramifications across diverse domains, and the significant insights it can provide to human. Embark on an intriguing exploration of the ant kingdom, where collaboration, communication, and decentralized decision-making coalesce to create a complex system that offers significant lessons for human pursuits.